2021
DOI: 10.3389/fnagi.2021.625843
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Cerebral Blood Flow Abnormalities in Subjective Cognitive Decline Plus: Diffusional Kurtosis Imaging and Three-Dimensional Arterial Spin Labeling Study

Abstract: Objective: To explore microstructural and cerebral blood flow (CBF) abnormalities in individuals with subjective cognitive decline plus (SCD plus) using diffusional kurtosis imaging (DKI) and three-dimensional (3D) arterial spin labeling (ASL).Methods: Twenty-seven patients with SCD plus, 31 patients with amnestic mild cognitive impairment (aMCI), and 33 elderly controls (ECs) were recruited and underwent DKI and 3D ASL using a GE 3.0-T MRI. Mean kurtosis (MK), fractional anisotropy (FA), mean diffusivity (MD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 100 publications
(121 reference statements)
1
22
0
Order By: Relevance
“…Currently, there is no consensus on which clinical and neuroimaging characteristics of individuals lead to a higher risk of developing SCD, despite the increasing research evidence about the clinical and cerebral microstructural and blood flow alterations associated with SCD ( Yang et al, 2021 ; Zhang et al, 2021). We speculate that the different findings may be related to the ethnic difference, different inclusion criteria, and factors analysis methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there is no consensus on which clinical and neuroimaging characteristics of individuals lead to a higher risk of developing SCD, despite the increasing research evidence about the clinical and cerebral microstructural and blood flow alterations associated with SCD ( Yang et al, 2021 ; Zhang et al, 2021). We speculate that the different findings may be related to the ethnic difference, different inclusion criteria, and factors analysis methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prospective cohort study displayed that patients with SCD showed a poor level of CBF in the right middle frontal gyrus compared with the HC subjects (Zhang et al, 2021). Participants with SCD plus demonstrated a significant decline in CBF values, mainly in the hippocampal head and posterior cingulate cortex ( Yang et al, 2021 ). Moreover, the study from the Amsterdam Dementia Cohort found that reduced CBF was not associated with worse performance in patients with SCD ( Leeuwis et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S ( n,b ) denotes the diffusion encoding direction n and the diffusion signal intensity of the diffusion-weighted b -value, S 0 denotes the diffusion signal intensity of b 0 , and D ij and W ijkl represent the components of the diffusion tensor and the diffusion kurtosis tensor, respectively. We have also used this DKI analysis method in our earlier studies ( Zheng et al, 2017 ; Yang et al, 2021 ). Multi-echo QSM data were processed by Laplacian-based phase unwrapping, and V-SHARP background field removal ( Li et al, 2014b ), and improved the sparse linear equation and least squares (iLSQR) method ( Li et al, 2015b ) to generate MS maps, based on the images of the last three echoes.…”
Section: Methodsmentioning
confidence: 99%
“…Findings by Falangola et al (Falangola et al, 2008) and Das et al (Das et al, 2017) demonstrate that kurtosis is negatively associated with age. Also, reduced MK has found to be associated with reduced cerebral blood flow and cognitive function (Tu et al, 2021;Yang et al, 2021), and has been demonstrated as a potential marker for early detection of amyloid pathology (Praet et al, 2018). However, published studies generally have small sample sizes and do not quantitatively examine DKI and DTI in conjunction.…”
Section: Kurtosis Associations With Agementioning
confidence: 99%